Pengaruh Kinerja Keuangan, Intensitas Aset Tetap, Dan Ukuran Perusahaan Terhadap Agresivitas Pajak - Islakhun Nisak, Islakhun; Luh Nadi (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2024)
This study aims to empirically determine the influence of financial performance, fixed asset intensity, and company size on tax aggressiveness in the consumer non-cyclicals manufacturing sector listed on the Indonesia Stock Exchange from 2018 to 2022. The sample selection used purposive sampling, resulting in 21 consumer non-cyclicals companies listed on the Indonesia Stock Exchange during the 2018-2022 period. The data analysis employed multiple regression analysis with data processing using Eviews 12SV software. The results show that financial performance has a significant partial influence on tax aggressiveness, while fixed asset intensity and company size do not have a significant influence. However, when considered together, financial performance, fixed asset intensity, and company size collectively influence tax aggressiveness.